Antifungal Activity and Potential Mechanism of 6,7, 4′-O-Triacetylscutellarein Combined With Fluconazole Against Drug-Resistant C. albicans - Su, Liu-Yan; Ni, Guang-Hui; Liao, Yi-Chuan; Su, Liu-Qing; Li, Jun; Li, Jia-Sheng; Rao, Gao-Xiong; Wang, Rui-Rui (Frontiers in Microbiology, 2021)
The increased resistance of C. albicans to conventional antifungal drugs poses a huge challenge to the clinical treatment of this infection. In recent years, combination therapy, a potential treatment method to overcome C. albicans resistance, has gained traction. This study assessed the effect of 6, 7, 4'-O-triacetyl baicalein (TA) combined with fluconazole (FLC) on C. albicans in vitro and in vivo. TA combined with FLC showed good synergistic antifungal activity against drug-resistant C. albicans in vitro, with a partial inhibitory concentration index (FICI) of 0.0188-0.1800. In addition, the time-kill curve confirmed the synergistic effect of TA and FLC. TA combined with FLC showed a strong synergistic inhibitory effect on the biofilm formation of resistant C. albicans. The combined antifungal efficacy of TA and FLC was evaluated in vivo in a mouse systemic fungal infection model. TA combined with FLC prolonged the survival rate of mice infected with drug-resistant C. albicans and reduced tissue invasion. TA combined with FLC also significantly inhibited the yeast-hypha conversion of C. albicans and significantly reduced the expression of RAS-cAMP-PKA signaling pathway-related genes (RAS1 and EFG1) and hyphal-related genes (HWP1 and ECE1). Furthermore, the mycelium growth on TA combined with the FLC group recovered after adding exogenous db-cAMP. Collectively, these results show that TA combined with FLC inhibits the formation of hyphae and biofilms through the RAS-cAMP-PKA signaling pathway, resulting in reduced infectivity and resistance of C. albicans. Therefore, this study provides a basis for the treatment of drug-resistant C. albicans infections.